Growth-promoting effect of alginate on Faecalibacterium prausnitzii through cross-feeding with Bacteroides - Ryuta Murakami; Nanami Hashikura; Keisuke Yoshida; Jin‐zhong Xiao; Toshitaka Odamaki (2021)
Faecalibacterium prausnitzii is a commensal gut bacterium that is thought to provide protection against inflammatory diseases. However, this bacterium is extremely oxygen sensitive, which limits its industrial application as a probiotic. The use of prebiotics to increase the abundance of this bacterium in the gut is an alternative strategy to achieve its possible health-promoting effect. We evaluated nine substances as candidate prebiotics for F. prausnitzii using a pH-controlled single-batch fermenter as a human gut microbiota model. Of them, alginate markedly increased the relative abundance of F. prausnitzii, as determined by the significant increase in the number of 16S rRNA sequences corresponding to this bacterial taxon in the fecal fermentation samples detected by real-time PCR. However, F. prausnitzii strains were incapable of utilizing alginate in monoculture, implying that an interaction with another gut microbe was required. There was a positive correlation between the relative abundance of F. prausnitzii and that of Bacteroides when cultured in medium containing alginate as the sole carbon source, indicative of cross-feeding between these bacteria. Interestingly, the ratio of acetic acid, a known substrate for F. prausnitzii, produced by Bacteroides was significantly higher in the alginate-containing medium than in media containing other prebiotic candidates. Bacterially degraded alginate oligosaccharides (AOS) remained in the medium after Bacteroides monoculture, and an isolate of F. prausnitzii was able to utilize a portion of them. Genomic sequencing revealed that the strain that consumed the AOS contained an ATP-binding cassette transporter, an alginate lyase, and AlgQ1/2 homologs encoding solute-binding proteins. Furthermore, in real-time PCR analyses, AlgQ1/2 homologs were detected in fecal samples collected from 309 of 452 (68.4%) Japanese subjects. Thus, the products of alginate assimilation by Bacteroides may promote the growth of F. prausnitzii.